"PBS : a major enabler for Systems Engineering": A thematic thinking by Thales Systèmes Aéroport3eAs. Issue 1 (June 2013) - Tonnellier, Edmond; Terrien, Olivier
Abstract: In 2012, Thales Systèmes Aéroportés initiated a study on the Product Breakdown Structure (PBS) as a central enabler for Systems Engineering. Obvious similarities between tree‐like representations used throughout the entire lifecycle of a Solution suggest in a simplistic and reductive way that breakdown structures are only an unnecessary redundancy due to complementary businesses designating the same reality in different ways. However, a more precise study of international standards and a more careful examination of stepped uses of these tree frames show how different their purposes are and how they support different features of the system being designed. Nevertheless a confusion exists between these tools. Thus our paper asks a question of principle: "does this confusion come from imprecise and unclear standards on this subject, from incorrect interpretations of these by system architects or from vague approximations in the use of technical tools that structure and size R&D projects?".